A 13-level switched-capacitor-based multilevel inverter with reduced components and inrush current limitation - Hossein Mansourizadeh; Majid Hosseinpour; Ali Seifi; Mahdi Shahparasti (Scientific Reports)
Abstract This paper proposed a hybrid switched-capacitor inverter to reduce the number of components and achieve automatic capacitor balancing. The proposed structure combines a switched capacitor (SC) unit with a flying capacitor (FC). Significant advantages of the proposed design include a reduced number of components, simple control, voltage boosting capability, and limitation of the inrush current during capacitor charging. The proposed structure used only eleven switches and three capacitors to generate 13 levels. Compared to other 13-level switched-capacitor inverters, the proposed structure utilizes fewer components, capacitors with lower maximum voltage, and fewer conduction components. The flying capacitor used in the proposed design can naturally balance at half of the input DC voltage (0.5Vdc), enabling sensor-free operation. Therefore, with simple control over the inherent voltage balancing of the capacitors, the structure requires only six switching signals, which reduces the overall system cost. Circuit performance analysis, automatic capacitor balancing, and the charging and discharging processes are introduced. Subsequently, a numerical comparison is made with recently proposed 13-level switched-capacitor inverters, demonstrating the advantages of reduced active components, simplified control, cost-effectiveness, and low power losses. Finally, simulation results are presented to confirm the performance of the proposed structure.